The Relationship between Academic Engagement, Lecturer’s Competence and Social Support to the Students’ Academic Achievement - Ateng Ruhendi; M Sandi Marta (AL-ISHLAH: Jurnal Pendidikan, 2022)
One of the goals of college is to educate students to have the ability to survive and advance in every development of the times. And among the skills that students must have is language mastery. Therefore, students need to have high academic engagement and support from the environment in which they study. This study aims to test the relationship of academic engagement to the achievement of Arabic learning achievement and test the effect of moderation of lecturer competence and social support on the relationship. Survey data was collected from 391 students of UIN Sunan Gunung Djati Bandung, which was further analyzed using hierarchical regression. The results showed that academic engagement statistically positively affects the achievement of learning Arabic.  Furthermore, lecturer competence and social support can strengthen academic engagement relationships and achievements in learning Arabic at UIN Sunan Gunung Djati Bandung.